2011
DOI: 10.3174/ajnr.a2681
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Evaluation and Visualization of Lumbar Foraminal Nerve Root Entrapment by Using Diffusion Tensor Imaging: Preliminary Results

Abstract: BACKGROUND AND PURPOSE: DTI can provide valuable structural information that may become an innovative tool in evaluating lumbar foraminal nerve root entrapment. The purpose of this study was to visualize the lumbar nerve roots and to measure their FA in healthy volunteers and patients with lumbar foraminal stenosis by using DTI and tractography with 3T MR imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
73
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(82 citation statements)
references
References 34 publications
8
73
1
Order By: Relevance
“…25,26 Thus, we applied a single ROI technique for the fibre tracking, in common with other previous studies on DTI of the peripheral nerves. 12,15,19 Our study had several limitations. First, our case series involved only healthy volunteers, and their age group was relatively young.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25,26 Thus, we applied a single ROI technique for the fibre tracking, in common with other previous studies on DTI of the peripheral nerves. 12,15,19 Our study had several limitations. First, our case series involved only healthy volunteers, and their age group was relatively young.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, this technique has also been applied to several peripheral nerves, namely the median nerve, 12 tibial nerve 13,14 and lumbar plexus. 15 Those studies demonstrated that the ADC and FA could reflect the pathological conditions of peripheral nerves. To date, only a few studies reported the application of DTI to the IAN.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 683 subjects were studied across 24 DTI articles. 177 patients with lumbar spinal canal stenosis (LSCS) in 5 articles 11,12,16,17,20) , 143 patients with lumbar disc herniation (LDH) in 7 articles 7,13,15,20,21,23,29) , 112 patients with lumbar radiculopathy in 3 articles 10,19,22) , 36 patients with foraminal stenosis (FS) in 6 articles 9,11,16,20,27,28) , 2 patients with lower back pain in one article 20) , 3 cases with diastematomyelia and one case with tethered cord in one article 30) , and one case with spina bifida in one article 26) were included. 7 post mortem subjects were investigated in one article 8) .…”
Section: Diffusion-weighted Mr Neurographymentioning
confidence: 99%
“…7 post mortem subjects were investigated in one article 8) . 201 healthy volunteers were also investigated in 15 articles 8,11,14,[16][17][18][19][22][23][24][25][26][28][29][30] .…”
Section: Diffusion-weighted Mr Neurographymentioning
confidence: 99%
See 1 more Smart Citation